Training Needs of Students' Parents for Mentoring and Counseling Programs - in Al-Makhwah Province - Al-Omar, Hussein Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the most important training needs for students' parents in general education schools in Al-Makhwah governorate in the Kingdom of Saudi Arabia and to identify the existence of statistically significant differences between the average of study individuals regarding the training needs due to the difference in the school stage for students' parents of students (primary, intermediate, secondary). The study used the descriptive-analytical method. The study population consisted of 420 parents in Al-Makhwah Governorate in the Kingdom.Results of the study came as follows: The arrangement of the training needs from counseling programs of students parents, the first phrase was: the definition of the growth characteristics of students, it was at a great level, from the results also there are statistically significant differences in the training needs of the students’ parents of the counseling programs due to the variable of the school stage for student's parents, there are statistically significant differences in favor of parents whose children study in intermediate schools.The recommendations reached by the study: the need for training courses for parents of students to be derived from their training needs for programs in the field of guidance and counseling, the need to provide continuous studies on a regular basis to determine training needs on the same category of parents to be a starting point for the development of current guidance and counseling programs or to develop training programs to meet this need.
Keywords: training; training needs; parents; mentoring and mentoring programs